The Seljuks of Anatolia: An epigraphic study - Azzam, Salma Moustafa (AUC Knowledge Fountain, 2017)
This is a study of the monumental epigraphy of the Anatolian Seljuk Sultanate, also known as the Sultanate of Rum, which emerged in Anatolia following the Great Seljuk victory in Manzikert against the Byzantine Empire in the year 1071. It was heavily weakened in the Battle of Kose Dag in 1243 against the Mongols but lasted until the end of the thirteenth century. The history of this sultanate which survived many wars, the Crusades and the Mongol invasion is analyzed through their epigraphy with regard to the influence of political and cultural shifts. The identity of the sultanate and its sultans is examined with the use of their titles in their monumental inscriptions with an emphasis on the use of the language and vocabulary, and with the purpose of assessing their strength during different periods of their realm. The analysis is implemented through a chronological perspective with the attempt to establish the earlier dynastic influences affecting the choices of titles, literary styles and epigraphic formulae. The history of the Anatolian Seljuks is traced chronologically through the monumental inscriptions of the era in question, from the beginning of the reign of Rukn al-Din Mas‘ud I which provides the earliest surviving Anatolian Seljuk numismatic epigraphy. The main analyses of monumental inscriptions cover the period from the reign of ‘Izz al-Din Kılıç Arslan III (1156-1192) to the reign of ‘Izz al-Din Kaykavus I (1246-1261). An assessment of the surviving monumental inscriptions of the wives of ‘Ala’ al-Din al-Din Kayqubad is included. The analyzed epigraphic material is linked to the development of the dynasty through its apogee until its defeat against the Mongols in the battle of Köse Dağ (1243). The chronological connections of Anatolian Seljuk inscriptions with historical events helps to understand the ideology and political motives of the dynasty. The inscriptions provide a clearer picture concerning the influences that might have shaped the royal identity of the Anatolian Seljuk dynasty. Moreover they defined the periods in which new titles were adopted by the Anatolian Seljuk sultans, and the differences that occurred in the structure, organization and vocabulary used in monumental inscriptions. The comparison of Anatolian Seljuk epigraphy with that of other contemporary and preceding dynasties enables us to detect the most important influences. The time frame of the analyzed inscriptions also allows for a conclusion regarding the effect of the battle of Köse Dağ on the use of royal titles, as well as the development in the Anatolian Seljuk sultanate's internal balance of power as a whole.